PENGEMBANGAN MEDIA AUDIO-VISUAL PEMBELAJARAN LARI JARAK PENDEK UNTUK SISWA SMP - -, Jaliusril -; Asyhar, Rayandra; Harjono, Hary Soedarto (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
This article is based on a developmental research. In the production step, the initial product was developed. This product was validated by an expert in subject matter and an expert in media. The next step was trying out the product to the students in three steps, namely, one-to-one try out, small group try-out, and field try-out. The subjects were students of SMP Negeri 3 Tanjung Jabung Timur in seventh grade. The subject in this research consisted of two students for one-to-one try-out, ten students for the small group try-out, and 31 students for the field try-out. The data collected in this research included the data from the subject matter expert, the evaluation data from the media specialist, and data from the students on the aspect of attraction. The data were collected using an interview sheet for the subject matter expert, the media expert, and questionnaire sheet for the one-to-one try-out, the small group try-out, and the field try-out. The data were analyzed using the descriptif analysis. The research results show that: 1) the development of audio-visual media Learning spint was in five phases, namely analysis, design, development, implementation, and evaluation, the quality of instructional media developed viewed from the content aspect is good, the quality from the developed instructional media in term of the appearance aspects is good. the quality of the developed instructional media in regard to the attraction aspect is interesting. Keyword: Audio-Visual Media, Pelajaran Lari Jarak Pendek SMP.